Taking Stock of China and the Geopolitics of Energy - Michal Meidan; Anders Hove; Philip Andrews-Speed (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2023)
China has a huge and growing influence on the global politics and economics of energy. The topic of China's role in the new geopolitics of energy is hardly new, but the supply chain crisis following Covid and then the Russian invasion of Ukraine in 2022 have combined to further elevate the topic. Decarbonization and the risk of de-globalization are increasingly central to energy policies and are framing the geopolitics of energy. China's energy security concerns are also closely linked to these trends: China is a leading importer of oil and gas, so its energy supplies are exposed to price volatility, which is exacerbated by supply shocks due to instability in producer countries, transportation bottlenecks, and sanctions. But as China has established itself as the world's leading manufacturer of renewable energy sources, and as the energy transition gathers momentum, China's energy security opportunities and challenges are evolving. From the point of view of advanced economies, China has long been viewed both as an economic partner and as an industrial competitor. Since the Paris Climate Agreement, China has been a central actor in climate diplomacy as well as a leader in clean energy, but China's dominance of clean energy supply chains has raised concerns about whether Western countries can catch up. For many years, the example of China's clean energy scale-up acted as a positive spur to more policy action, but since 2020 these efforts have taken on a more urgent and confrontational aspect as governments explicitly target reducing China's dominance in specific technologies (batteries, solar) and critical materials. In other world regions, attitudes towards the role of China in energy geopolitics are vastly different and are informed, in part, by the deepening rift between China and the US. The rapidly changing role of China in world energy politics makes it important and timely to review the topic. In this issue of the Oxford Energy Forum, we present insights and views from experts from around the world, showcasing the broad range of views on China's geopolitical position and trajectory. The issue discusses the role of China and perceptions of it in the geopolitics of hydrogen, renewables, power grids, minerals, finance, and carbon, combined with regional perspectives from Russia, the US, the Middle East, Africa, South-East Asia, and India.
Keywords: 330